Behaviors of Thin-Walled Cylindrical Shell Storage Tank under Blast Impacts - Shengzhuo Lu; Wei Wang; Weidong Chen; Jingxin Ma; Yaqin Shi; Chunlong Xu (Shock and Vibration)
Large steel storage tanks designed with long-span structures, employed for storing oil and fuel, have been widely used in many countries over the past twenty years. Most of these tanks are thin-walled cylindrical shells. Owing to the high risk of gas explosions and the resulting deaths, injuries, and economic losses, more thorough damage analyses of these large structures should be conducted. This study examines the structural response of a simplified steel storage tank under a blast impact, as calculated by the LS-DYNA software package. The numerical results are then compared with a scale-model experiment. On that basis, the simplified storage tank prototype, which has a 15 × 104 m3 capacity, is analyzed using numerical simulation. In this study, we address issues around the variation in structural responses—particularly of the failure mode, resultant displacement, structural energy, and dynamic strain under the impact. In addition, we also discuss the effects of varying the internal liquid level, constraint conditions, and blast intensity.